Rapıd Canıne Dıstalızatlon Wıth The Use Of Perıodontal Dıstractıon Osteogenesıs Technıque (A Prelımınary Case Report) - Seher Sayın; Osman Bengi; Hüseyin Ölmez; Ümit Gürton; Deniz Sağdıç (Galenos Yayinevi, 2003)
When distraction osteogenesis technique is used for orthodontic tooth movement it is called periodontal distraction osteogenesis. Orthodontic tooth movement is a periodontal fenomen which is characterizied with alveolar bone resorption on the pressure side and alveolar bone deposition on the tension side. After the mechanical stimulus, periodontal ligament is stretched (distracted) and followed by alveolar bone deposition (osteogenesis). In our study a rapid canine distalization case is presented in which periodontal distraction osteogenesis technique is used by an intraoral tooth-born distractor which is developed in our clinic. It is tought that this new technique, which decreases the canine distalization process in a short period such as 3-4 weeks, is going to be common in the future, when supported with clinical and histological studies.